Public perception on COVID-19 vaccination intention - Zaid Zaid; Katon Pratondo (Intelektual Pustaka Media Utama, 2021)
To resolve the health crisis caused by coronavirus disease (COVID-19), the Indonesian government is trying to implement a mandatory vaccination policy for all Indonesians. It was just that the success of this policy is largely determined by acceptance preceded by the public intention to be vaccinated, in which public perception plays a major role in determining intention. This research, therefore, aimed to evaluate and examine the role of perceived risk, benefit, and susceptibility on the COVID-19 vaccination intention. By using a cross-sectional approach, this quantitative study involved 98 participating respondents who were determined by the purposive sampling method. The results of this study finally found and proven that perceived risk (coefficient β=0.290 and T-value 2.456 with p-value=0.011), perceived benefits (β= 0.394 and T-value 3.873 with p-value=0.000), and perceived susceptibility (β=0.233 and T-value 3,230 with p-value=0.001) had a positive and significant effect on the COVID-19 vaccination intention.